Streptomyces marincola sp. nov., a Novel Marine Actinomycete, and Its Biosynthetic Potential of Bioactive Natural Products - Shi, Songbiao; Cui, Linqing; Zhang, Kun; Zeng, Qi; Li, Qinglian; Ma, Liang; Long, Lijuan; Tian, Xinpeng (Frontiers in Microbiology, 2022)
Marine actinomycetes are an important source of antibiotics, but many of them are yet to be explored in terms of taxonomy, ecology, and functional activity. In this study, two marine actinobacterial strains, designated SCSIO 64649T and SCSIO 03032, were isolated, and the potential for bioactive natural product discovery was evaluated based on genome mining, compound detection, and antimicrobial activity. Phylogenetic analysis of the 16S rRNA gene sequences showed that strain SCSIO 64649T formed a single clade with SCSIO 03032 (similarity 99.5%) and sister clades with the species Streptomyces specialis DSM 41924T (97.1%) and Streptomyces manganisoli MK44T (96.8%). The whole genome size of strain SCSIO 64649T was 6.63 Mbp with a 73.6% G + C content. The average nucleotide identity and digital DNA–DNA hybridization between strain SCSIO 64649T and its closest related species were well below the thresholds recommended for species delineation. Therefore, according to the results of polyphasic taxonomy analysis, the strains SCSIO 64649T and SCSIO 03032 are proposed to represent a novel species named Streptomyces marincola sp. nov. Furthermore, strains SCSIO 64649T and 03032 encode 37 putative biosynthetic gene clusters, and in silico analysis revealed that this new species has a high potential to produce unique natural products, such as a novel polyene polyketide compounds, two mayamycin analogs, and a series of post-translationally modified peptides. In addition, other important bioactive natural products, such as heronamide F, piericidin A1, and spiroindimicin A, were also detected in strain SCSIO 64649T. Finally, this new species’ metabolic crude extract showed a strong antimicrobial activity. Thanks to the integration of all these analyses, this study demonstrates that the novel species Streptomyces marincola has a unique and novel secondary metabolite biosynthetic potential that not only is beneficial to possible marine hosts but that could also be exploited for industrial applications.